Edible films as carrier for lactic acid bacteria - Pereira, Joana Odila (2017)
The use of edible coatings and films formulated with bioactive compounds in food products in order to convey new functionalities or extend shelf-life opens new possibilities as a carrier for functional lactic acid bacteria. In this work the main objective was to study the stability of probiotic microorganisms, viz. Bifidobacterium animalis Bb-12® and Lactobacillus casei-01, in edible film formulations based on whey protein isolate (WPI). The results demonstrated a loss of bacterial cell viability of ca. 3 log cycles (reaching 106 CFU/g film) until 60 d at both 23 and 4 C, noting that the most marked decrease was at 23 C for both strains. Bifidobacterium animalis Bb-12® remained viable for a longer period of time and with less decrease in its cell numbers (108 CFU/g film). Physical properties, namely color, water activity, thickness, young’s modulus, tensile strength, elongation at break and the molecular structure of WPI films were maintained stable throughout the storage period at both temperatures tested. Edible films incorporated with probiotics can be good carriers for these to be ingested together with food products.